Implementasi Sistem Moving Class Mastery Learning (MCML) di MA Al Irsyad Berbasis Pesantren : Inovasi Pembelajaran untuk Meningkatkan Kompetensi dan Karakter Siswa - Suhendi Mubarok; Siti Qomariyah; Wahid Nurwaluyadin Sofyan (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
Education in the modern era requires innovative approaches to address challenges such as ensuring equal comprehension among students. The Moving Class Mastery Learning (MCML) system implemented by MA Al Irsyad Berbasis Pesantren combines moving class and mastery learning approaches. MCML ensures students deeply understand concepts before progressing to new material, supported by digital technology and specialized teacher training. Initial results show significant improvements in learning motivation and student achievement, with 85% achieving optimal mastery levels. As a pesantren-based institution, MA Al Irsyad integrates the national curriculum with religious studies, emphasizing character education, entrepreneurship, bilingual programs, and local cultural arts training. Comprehensive evaluations ensure academic and character development. This approach reflects MA Al Irsyad's commitment to nurturing religious, competent individuals ready to meet global challenges.